Candidate Selection Using Visual Symmetric Key Cryptographic Approach in Online Election Process - prakasha, Krishna; Acharya, Vasundhara (International Journal of Engineering and Technology, 2018)
In the candidate selection process in polling, security is an important aspect. To protect the confidential information from unsuspecting victims for identity theft and other fraudulent activities, the authentication of images using visual cryptography is implemented in the proposed research work. An intelligent approach for polling and selecting a leader is proposed using cryptographic techniques. The process involves two phases namely management phase and client phase with some public key infrastructure techniques. The management phase will authenticate the user and generates one share of the image and it is a claimant process. The client phase is a verifier process where after authentication, the user gets another half. The elector needs to merge both the halves to succeed.Â Â